Caudacalanus (Copepoda, Calanoida): a new benthopelagic genus from the abyssof the tropical South Atlantic and Southern Ocean - Markhaseva, Elena L.; Schulz, Knud (Zootaxa, 2008)
Two species of a new spinocalanoidean genus, Caudacalanus, are described from female specimens collected during the German expeditions ANDEEP I–II in 2002 and DIVA-1 in 2000 at abyssal depths above the seabed in the Southern Ocean and tropical waters of the South Atlantic. Segmentation and setation of swimming legs of the new genus are typical of the superfamily Spinocalanoidea. Caudacalanus gen. nov. shares the derived morphology of the oral parts and P1 basis and endopod with a monophyletic group of genera, viz. Arctokonstantinus, Foxtonia and Sognocalanus. Arctokonstantinidae is available for this lineage. The new genus differs from other spinocalanoideans by strong asymmetry of the caudal rami, with the right ramus nearly twice as long and wide as the left; setation of maxillule exopod reduced to 0–1 seta; maxilla basis lacking any setae; and maxilliped basis with 1 seta and endopod reduced to 3 segments.